Sifat Kimia Kayu Jati (Tectona grandis) pada Laju Pertumbuhan Berbeda (Chemical Properties of Teak Wood on Different Growth-rates) - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2010)
Chemical properties of 32 teak woods representing 3 different diameter classes (slow, medium, and fast growth-rate) at the same age class were evaluated. The content of cell wall component and extractives of outer heartwood part were determinated according to ASTM and TAPPI standard. The extractives components of wood were characterized by Gas-Chromatography Mass-Spectrometry (GC-MS). By analysis of variance, there was not significant difference among the growth-rate in the content of holocellulose, α-cellulose, pentosan, Klason lignin, acid soluble lignin, ash, and hot-water soluble extractives. The diameter class significantly affected the ethanol-benzene soluble extractives which faster growth-rate trees tend to have higher values than those of slower growth-rate trees. However, based on GC and GC-MS, there was not significant differences in the levels of major components of ethanol-benzene extracts both of quinones (deoxylapachol and its isomer, lapachol, tectoquinone, and tectol) and non-quinones (palmitic acid and squalene).